NMR and AFM study of the G-quadruplex DNA - Adrian, Michael (2009)
G-quadruplex is a DNA conformation formed from guanine-rich strands. The rotation rates of guanine's amino protons in different G-tetrads of the d(TTAGGGG)4 dimeric and monomeric configurations have been determined by 2D NOESY NMR line-shape analysis. The amino protons of G7 at the dimeric interface was found to rotate about 10 times faster in the monomer than in the dimer. The activation energies of G7 amino protons in the monomer and dimer were 85.7 kJ/mol and 72.4 kJ/mol, respectively. This characterizes the stacking interaction in G-quadruplexes and thus can be used to monitor the binding of ligands. On the other hand, our AFM study of G-quadruplex DNA revealed that the concentration and the type of cation were the major factors for the higher-ordered structure of aggregated G-wires to be generated. The phase diagram of d(G4T2G4)4 superstructure in Mg2+ buffer is reported in this work.